Texas Gulf Sulphur Beneficiation Of North Carolina Phosphate - Thomas J. Wright (Society for Mining, Metallurgy & Exploration, 1971)
The evaluation and development of the Eastern North Carolina phosphate deposit resulted in one of the world's largest and most modern phosphate mines and fertilizer complexes at an investment in excess of $90,000,000. The resulting ore beneficiation process showed excellent correlation with pilot plant data. A number of variations from current industrial practices were introduced and projected from bench scale tests through pilot plant to production. Principal among these variations were the following: 1) removal of magnesium by classification, 2) simultaneous flotation of coarse and fine phosphate, 3) the use of saponified fatty acid, 4) utilization of filter wash water for deoiling, 5) utilization of a rougher concentrate for acidulation, 6) calcination of flotation concentrates, and 7) elimination of grinding prior to the manufacture of phosphoric acid.